The Influence of the Problem Posing Approach on the Creative Thinking Ability of Class V Students on Geometry Material at Elementary School - Suryaningsih, Tri; Sabila, Aulia Ida; Widiyanto, Rohmat; Herianingtyas, Nur Luthfi Rizqa; Siron, Yubaedi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2025)
The 21st century require students to have the ability to think creatively, i.e. come up with original ideas and innovative solutions in various situations. However, the creative thinking skills of Indonesian students are still low, shown through the lack of variety of ideas and the tendency to think linearly in solving problems. This study aims to determine the influence of the problem posing method on the mathematical creative thinking ability of fifth grade elementary school students regarding fifth grade geometry. The research method used in this study is a quasi-experimental method with a Randomized Control Group Post Test Only. This research was conducted at SDN Tanah Baru 02. Sampling was carried out using the Simple Random Sampling technique which amounted to 30 people. The research instrument used in this study is a test instrument that measures students' mathematical creative thinking skills on spatial building materials. The test consisted of 9 questions in the form of descriptions. Each question represents an indicator of creative thinking according to Munandar, which is taught using the problem posing method. The average result of the creative thinking ability obtained using the problem posing method of the experimental class was 72.70, and the mathematical creative thinking ability of the control class students was 51.73. The results of the calculation of the T-test using the Independent Sample T-test method in the post-test results of the second class obtained a significance value of 0.000 < 0.05, so that H0 was rejected and H1 was accepted, which means that the Problem Posing approach affects students' mathematical creative thinking skills. This research shows that the problem posing method can be used as an alternative learning strategy to foster students creative thinking skills, thereby supporting the achievement of 21st century competencies in the elementary school curriculum.